Hanging Planning’s Dirty Laundry - DePiano, Lisa; Nagel, Kiara; fonza, annalise (UnderCurrents: Journal of Critical Environmental Studies, 2007)
Ducking under the little cards attached to a string tied taut between a tree and the Landscape Architecture building, a young white man asks, "What is this? What are you guys doing?" He stops to read the card aloud: